Hadrian's Wall : exploring its past to protect its future - Alberti, Marta,; Mountain, Katie, (Archaeopress Roman archaeology ;, 2022)
Celebrating the 1900th anniversary of Hadrian's visit to Britain and the building of the Wall, this book presents studies from from the point of view of those living, visiting, researching and working along it. The book offers a realistic discussion of current issues and solutions in the exploration, management and protection of Hadrian's Wall.